Tratamento cirúrgico do schwannoma traqueal - Torres,Orlando Jorge Martins (2002)
Schwannoma is a rare benign tumor of the proximal tracheobronchial tree. The aim of the present study is to report a case of tracheal schwannoma causing airway obstruction. A 16-year-old woman complained of cough, wheezing and dyspneia. Bronchoscopy and computerized tomography showed a polypoide intratracheal mass obstructing approximately 80% of the lumen. The treatment consisted of tracheal resection and primary anastomosis. Histological analysis revealed a tracheal schwannoma. The postoperative course was uneventful and the patient remains well twelve months after surgery.